The Use Of Legal Morals To Prevent Women's Violence In The Educatory Environment - Arif, Alvia Zuman Zauza; Rafid, Rahmad; Ali, Moh; Rahmawati, Alfi Mufida; Rizki, Muhammad; Kumala, Milka (International Journal of Sustainable Law, 2024)
Violence against women in the educational environment is a worrying issue because it has a direct impact on human rights, psychological development, and the sustainability of victims ' education. This study aims to analyze the application of moral law as a strategic approach in tackling violence against women in educational institutions. Using the juridical-sociological method, this study examines the relevance of applicable legal norms, such as Law Number 12 of 2022 on sexual violence crimes, with the application of legal moral values in the field. The results show that legal morality plays an important role in encouraging stakeholders to not only abide by the rules, but also internalize the values of justice, respect for human dignity, and protection of victims. The findings also revealed the existence of obstacles in the implementation of moral law, such as lack of legal awareness, lack of supervision, as well as structural barriers in the handling of cases of violence. Therefore, collaboration between educational institutions, governments, and communities is necessary to create a safe and inclusive educational environment. This study recommends the establishment of a special team in the educational environment that serves as a supervisor and facilitator of the application of legal morals, morality training for educators, as well as the provision of assistance services for victims. With effective implementation, moral law can be a strategic foundation to reduce the number of violence against women and realize equality in the educational environment